Isoconversional kinetic analysis of ring-opening polymerization of ε-caprolactone: Steric influence of titanium(IV) alkoxides as initiators - Meelua W. (2014)
Four titanium(IV) alkoxides, namely: Ti(IV) npropoxide (1), Ti(IV) n-butoxide (2), Ti(IV) tert-butoxide (3), and Ti(IV) 2-ethylhexoxide (4), have been used as initiators in the bulk ring-opening polymerization (ROP) of ε-caprolactone (ε-CL). The influence of the alkoxide group on the course of the ROP of ε-CL was investigated by means of 1H-NMR and differential scanning calorimetry (DSC). The 1H-NMRspectra confirmed that the ROP reaction of ε-CL proceeded via the widely accepted oordinationinsertion mechanism for each of the four initiators. Isoconversional methods have been used to evaluate non-isothermal DSC data via the equations of Friedman, Kissinger-Akahira- Sunose (KAS) and Ozawa-Flynn-Wall (OFW). The kinetic studies showed that the polymerization rate for the four initiators (1-4) was in the order of 1>24>3. The lowest activation energies (40-47, 42-44, and 49-52 kJ/mol for the Friedman, KAS and OFW methods respectively) were found in the polymerizations using Ti(IV) n-propoxide (1), while the highest activation energies (84-107, 77-87, and 80-91 kJ/mol for the Friedman, KAS and OFW methods respectively) were obtained using Ti(IV) tert-butoxide (3). Differences in the rates of polymerization and the activation energies amongst the four initiators appeared to be governed mainly by the different degrees of steric hindrance in the initiator structure. These results represent important findings regarding the steric influence of the alkoxide groups on the kinetics of the ROP of ε-CL initiated by titanium(IV) alkoxides. © 2012 Springer Science+Business Media B.V.